The prognostic impact of circulating tumor cells in subtypes of metastatic breast cancer - Wallwiener, Markus; Schott, Sarah; Marmé, Frederik; Sohn, Christof; Schneeweiss, Andreas (Breast cancer research and treatment, 2013)
The detection of circulating tumor cells (CTCs) in the peripheral blood of metastatic breast cancer (MBC) patients is an independent marker of prognosis. This large prospective multicenter study aimed to assess the impact of CTCs on overall survival (OS) and progression free survival (PFS) in patients with predefined molecular subgroups of MBC. To this end, 468 MBC patients were divided into three subgroups based on immunohistochemical staining of the primary tumor: (1) hormone receptor-positive/HER2-negative (HorR+/HER2−), (2) HER2-positive (HER2+), and (3) HorR-negative/HER2-negative (HorR−/HER2−) patients. CTC status (<5 CTCs/7.5 ml blood (CTC-negative) vs. ≥5 CTCs/7.5 ml blood (CTC-positive)) was determined using the CellCearch® system before patients started a new line of therapy. At baseline, 205 (42 %) patients were CTC-positive. On multivariate analysis, CTC-positivity was an independent prognostic factor for shorter PFS and OS. In HorR+/HER2− patients, median PFS [95 % CI] of CTC-negative versus CTC-positive patients was 8.60 [5.93-11.27] versus 4.33 [3.29-5.38] months (p < 0.001), in HER2+ patients 7.60 [5.40-9.79] versus 6.60 [4.20-9.00] months (p = 0.477) and in HorR−/HER2− patients 5.83 [5.09-6.78] versus 3.05 [1.81-4.29] months (p < 0.001), respectively. Median OS [95 % CI] of CTC-negative versus CTC-positive patients was as follows: not reached by either in the HorR+/HER2− subgroup (p < 0.001), not reached versus 18.07 [11.10-25.05] months (p = 0.001) in the HER2+ subgroup, and not reached versus 8.57 [4.07-13.07] months in the HorR−/HER2− subgroup (p = 0.001). In conclusion, our results strongly confirm the independent prognostic value of CTC enumeration in MBC patients. In contrast to recent reports, there was no association between primary tumor-based molecular subgroups and the impact of CTC status on OS. Hence, CTC status may help to identify patients who require aggressive therapy, especially among those with triple-negative MBC.
First online: 28 December 2012
Gesehen am 22.06.2018